Cardiopulmonary Anatomy & Physiology: Essentials of Respiratory Care, 7th Edition - Terry Des Jardins (Cengage Learning, 2019)
Prepare for a career as a leading respiratory therapist with the solid foundation in anatomy and physiology found in Des Jardins' best-selling CARDIOPULMONARY ANATOMY & PHYSIOLOGY: ESSENTIALS OF RESPIRATORY CARE, 7E. This extremely reader-friendly presentation delivers the most complete, accurate information about the structure and function of the respiratory system. Clear, concise coverage presents even complicated concepts in an understandable format using full-color design and proven learning features that guide readers in applying what they've learned to professional careers. Thirteen new Clinical Connections add to the book's total 141 Clinical Connections -- linking chapter content to today's clinical setting and highlighting actual situations that respiratory therapists encounter every day. These features also direct meaningful discussion and strengthen critical-thinking skills. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.